One size fits all? Experimental evidence on the digital delivery of personalized extension advice in Nigeria - Arouna, A.; Michler, J.D.; Yergo, W.G.; Saito, Kazuki (Wiley, 2021)
Blanket advice on optimal fertilizer application rates has failed to achieve potential yield gains for crop production in much of Sub‐Saharan Africa. However, digital technology now makes it possible to deliver personalized extension services to farmers at a much lower cost. We present results from a randomized control trial designed to evaluate the effectiveness of a mobile application that provides personalized advice on rice nutrient management. We find that households who were just given the personalized advice increase their yield by 7% and increase their profit by 10%. On average, personalized advice increases yields without increasing the overall quantity of fertilizer used. We conclude that the scaling of personalized extension services could improve productivity and livelihoods in Sub‐Saharan Africa without necessarily increasing the total amount of fertilizer in use.